Combination Effect of Golden Snail Powder and Fermented Coconut Cake on Quality of Duck Eggs - Nurmauliah Syaharuddin; Rasdyanah Rasdyanah; Dwi Kesuma Sari; Waode Santa Monica; Abdul Wahid Jamaluddin (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
This study aims to determinate the effect of combination golden snail powder and fermented coconut cake on quality of duck eggs. We were using experimental feeds combination form golden snail powder and fermented coconut cake as raw material for livestock rearing for duck. This research was conducted in July - September 2018 in Mangkoso Village, Barru Regency and continued with sample testing at the Laboratory Animal Husbandry Faculty of Livestock Product Technology University of Hasanuddin. This study used 16 female duck who are 20 weeks old with four types of treatments consists of four replications of each treatment. The egg quality was carried out using a sample of 16 eggs from Ducks which was maintained and treated with different rations. The data obtained were analyzed using variance analysis with a Completely Randomized test for significant different results. The results of the combination of golden snail powder and fermented coconut cake on egg color, egg white index, egg yolk index, haugh unit (HU) value of egg units. All treatments (P1, P2, P3) gave effect to three parameters, namely eggshell quality, egg yolk index and egg yolk color, while the other three parameters namely egg weight, egg white index and Haugh Unit (HU) value did not differ significantly from negative controls. The best treatment was shown by treatment P3 which gave an effect on the heavier egg weight than other treatments, eggshell quality grade A, Egg White Index and Egg Yolk Index showed good quality and bright golden egg yolks.